Inductive Reasoning (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the role and significance of inductive reasoning in the professional activity of legal practitioners. The application of inductive inference in law-making and in addressing legal gaps is examined through methods such as analysis, synthesis, comparison, and document analysis. The study provides a comprehensive overview of the role of the inductive method in reasoning, examining its types—including complete and incomplete induction, general (enumerative) induction, scientific induction—and their respective methodologies within a complex approach. The article also highlights the importance of identifying causal relationships in developing professional legal competencies.